2014
DOI: 10.1080/09658211.2014.881881
|View full text |Cite
|
Sign up to set email alerts
|

Does the thought of death contribute to the memory benefit of encoding with a survival scenario?

Abstract: Four studies tested whether the thought of death contributes to the survival processing advantage found in memory tests (i.e., the survival effect). In the first study, we replicated the "Dying To Remember" (DTR) effect identified by Burns and colleagues whereby activation of death thoughts led to better retention than an aversive control situation. In Study 2, we compared an ancestral survival scenario, a modern survival scenario and a "life-after-death" scenario. The modern survival scenario and the dying sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
1
8
0
2
Order By: Relevance
“…For example, Popp and Serra suggested that encountering specific animate items could trigger thoughts of predation or hunting, which could then trigger thoughts of death or dying, or mortality salience. The relation between memory and mortality salience, or Bdying to remember,^was originated by Hart and Burns (2012) and replicated by Bugaiska, Mermillod, and Bonin (2015), where it was found that thoughts of one's own death led to increased memory for items encoded after the thought induction. Burns, Hart, and Kramer (2014) and Bugaiska et al (2015) further found similar or higher levels of retention in various Bdeath processing^scenarios when compared to the traditional survival processing scenario, suggesting that thoughts of mortality salience increase memory.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Popp and Serra suggested that encountering specific animate items could trigger thoughts of predation or hunting, which could then trigger thoughts of death or dying, or mortality salience. The relation between memory and mortality salience, or Bdying to remember,^was originated by Hart and Burns (2012) and replicated by Bugaiska, Mermillod, and Bonin (2015), where it was found that thoughts of one's own death led to increased memory for items encoded after the thought induction. Burns, Hart, and Kramer (2014) and Bugaiska et al (2015) further found similar or higher levels of retention in various Bdeath processing^scenarios when compared to the traditional survival processing scenario, suggesting that thoughts of mortality salience increase memory.…”
Section: Discussionmentioning
confidence: 98%
“…研究者认为我们的记忆系统在物竞天择适者生存的进化过程中被不断塑造 (Klein, Cosmides, Tooby, & Chance, 2002;Tooby & Cosmides, 1992),因此记忆系统可能进化得使我们更容易记住那些能够帮助我 们生存繁衍的信息。从这个观点出发 Nairne 等人发现,在想象一个生存相关场景之后,被试的回想成绩 显著高于想象其他场景的被试,即生存加工的记忆优势效应 (Nairne, Thompson, & Pandeirada, 2007)。随后 有研究者对 Nairne 的实验进行改进和延伸, 证实了记忆的生存加工优势效应确实存在 (Burns, Hart, Griffith, & Burns, 2013;Klein, 2012)。另外,研究者们还发现不仅仅是针对文字,在刺激材料为图片时,依然存在 生存加工优势效应 (Otgaar, Smeets, & Van, 2010)。 Hart 等人发现与生存加工的优势效应类似, 死亡启动的条件下被试的回想成绩也会更好 (Hart & Burns, 2012)。之后 Hart 等人进行了一系列的实验比较生存加工和死亡加工对记忆影响的异同,他们发现和控制 组相比,生存加工和死亡加工对记忆有着类似的促进作用 (Burns et al, 2013;Burns, Hart, Kramer, & Burns, 2014)。之后有另外一些研究也支持了他们的结论 (Bugaiska, Mermillod, & Bonin, 2015)。同时有另外一些 研究的结果表明死亡加工虽然能促进记忆但却和生存加工是不同的 (Bell, Röer, & Buchner, 2013;Klein, 2014…”
Section: 研究背景unclassified
“…He also suggested that survival- and death-related thoughts might rely on different mechanisms to achieve their effects. A more recent paper summarized the controversy on this topic, concluding that the idea that survival's mnemonic effect was due to activation of thoughts of death was not readily supported, though there was some overlap between survival and death processing (Bugaiska et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the DTR effect reported by Hart and Burns ( 2012 ) was observed in a priming task, in which participants first thought about death and then processed words regarding their pleasantness without encoding their survival or death value. It is conceivable that the effect of priming on recall, as observed in DTR studies, differs from the effect of processing during survival-related tasks (Bugaiska et al, 2015 ). Although some studies have directly compared the survival-processing scenarios with the death-processing scenarios and found both to produce similar recall levels (Burns et al, 2014a ), to our knowledge, no study to date has directly compared the survival-priming scenarios with the death-priming scenarios.…”
Section: Introductionmentioning
confidence: 99%